SOSIALISASI PEMANFAATAN LARVA BLACK SOLDIER FLY (BSF) PADA PENINGKATAN BOBOT BADAN TERNAK - Lois (Jurnal Pengabdian Bukit Pengharapan, 2021)
Black Soldier Fly (BSF) is a feed ingredient that has a high protein content so that it has the potential to be used as feed for livestock. The increasing price of protein sources and environmental pressures, as well as the increasing demand for protein in the market have caused the price of animal-based protein to become increasingly expensive. The purpose of this service is to socialize Black Soldier Fly (BSF) larvae animal feed as a solution for animal feed. The method of implementation is to introduce the Black Soldier Fly (BSF), how to raise BSF flies, and the use of maggot as animal feed through counseling or socialization with the community in Pardamean Village in front of local community leaders and showing the cages of BSF flies that have been cultivated. The results of monitoring and evaluation showed that the people in Pardamean Village were enthusiastic in participating in these activities. The implementation of this socialization provides knowledge to increase and influence the weight of the average as well as to reduce organic waste generated by households.